1995
DOI: 10.1145/224057.224066
|View full text |Cite
|
Sign up to set email alerts
|

Serverless network file systems

Abstract: In this paper, we propose a new paradigm for network file system design, serverless network file systems. While traditional network file systems rely on a central server machine, a serverless system utilizes workstations cooperating as peers to provide all file system services. Any machine in the system can store, cache, or control any block of data. Our approach uses this location independence, in combination with fast local area networks, to provide better performance and scalability than traditional file sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(7 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The simulator of the hint-based and ideal algorithms we wrote ourselves. We obtained the N-Chance simulator from the developers of that system, and modified it to incorporate additional functionality employed in the xfs file system [Anderson et al 1995]. In the modified system, a manager preferentially forwards a request to the client caches instead of a server, improving the cooperative caching hit rate and reducing the server load.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulator of the hint-based and ideal algorithms we wrote ourselves. We obtained the N-Chance simulator from the developers of that system, and modified it to incorporate additional functionality employed in the xfs file system [Anderson et al 1995]. In the modified system, a manager preferentially forwards a request to the client caches instead of a server, improving the cooperative caching hit rate and reducing the server load.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The xfs file system uses a refined version of N-Chance [Anderson et al 1995]. A subsequent paper by Feeley et al [1995] described the Global Memory Service (GMS) that provides better performance than N-Chance as well as reduced overhead.…”
Section: Previous Cooperative Cachesmentioning
confidence: 99%
“…The researchers presented only simulation result, and their simulation result showed that cooperative cache reduces disk access by 50%, and read latency by at most 73%. Later, the cooperative cache was implemented in a Serverless Network File System [5]. 2) SSD as a Cache: A hybrid drive [6] is a NAND flash memory attached disk.…”
Section: A Dm-cachementioning
confidence: 99%
“…We use the centre server to organize all the storage nodes, but the centre server don't must be highly reliable. Many papers [12] [13] have discussed how to construct a serverless network file system by distribute the system service to all the storage nodes. Those methods are suitable for our system too.…”
Section: Prototype Descriptionmentioning
confidence: 99%